Photochemistry of compounds of the main group elements - KELLY, JOHN MOFFAT (My University, 1979)
Photochemistry of Compounds of the Main Group Elements BY J. M. KELLY 1 Introduction Reports on the photochemistry of inorganic anions are discussed in the next section; those dealing with other compounds are considered under the particular element. 2 Anions Irradiation (A > 340 nm) has no ...
PUBLISHED
Keywords: Chemistry